A multicentric observational single arm study to evaluate the effectiveness of toothpaste containing fluoro calcium phosphosilicate (Biomin) in the long-term relief of dentine hypersensitivity - Mishra, Amit; Suryawanshi, Varun; Thaper, Rakesh (International Journal Of Community Medicine And Public Health, 2025)
Background: Dentin hypersensitivity (DH) is an acute, transient pain from exposed dentin in response to stimuli not attributable to other dental defects or diseases. Among treatment options, fluoro-calcium phosphosilicate (Biomin) toothpaste has shown promising results in recent studies. The objective was to evaluate the long-term effectiveness, safety, and tolerability of Biomin toothpaste in Indian patients with DH. Methods: This was a prospective, investigator-initiated, multicenter, single-arm, open-label, observational study. Patients used the investigational toothpaste (Hydent Pro) twice daily for 24 weeks. Endpoints included changes in SCASS, VAS pain scores, DHEQ-15, gingival health and supra-gingival plaque scores. Safety and tolerability were monitored throughout. Results: A total of 121 patients (male: female, 71:50; mean age, 41.1 years) were enrolled. At week 24 significant (p<00.001) reductions were observed in SCASS (−1.8), VAS (−57.9), DHEQ-15 (−51.3) scores, and both mean Gingival health and supra-gingival-plaque scores also declined significantly (p<0.001) by -1.8, respectively. Investigators rated the effectiveness and tolerability of the toothpaste as excellent to very good in 89.9% and 92.5% patients respectively. No adverse events or other pharmacovigilance relevant information were reported. Conclusion: Twenty-four weeks of Biomin toothpaste treatment resulted in significant sensitivity relief. Improved overall oral-health-related quality of life; gingival health and anti-plaque action highlight its long-term therapeutic value. Moreover, 24 weeks of treatment with Biomin toothpaste was well-tolerated and can be an effective therapeutic option in the management of DH.